Comparative Study of The European Union's Digital Services Act (DSA) and Electronic Information and Transaction Law No. 1 of 2024 on Alleged Violations of Child Protection on The TikTok Platform - Arsyad Fakhri Zainuddin; Diana Setiawati (Proceeding International Conference Restructuring and Transforming Law, 2025)
This research discusses the fundamental differences between the European Union's Digital Services Act (DSA) and the Electronic Information and Transaction Law No 1 of 2024 in the context of child protection. The European Union's Digital Services Act regulates online platforms with a holistic and comprehensive approach, while the Electronic Information and Transaction Law No. 1 of 2024 focuses more on the Indonesian context. This research uses a qualitative method with a normative juridical approach. The normative juridical approach is an approach that is carried out based on the main material by examining laws and regulations, theories, concepts, legal principles related to differences in regulatory approaches, implementation, and their impact on child protection on the TikTok platform with descriptive-analysis. The difference between this article and previous research lies in the comparative study of data review. The objectives of this study are (1) to examine the fundamental differences between the European Union's Digital Services Act and the Electronic Information and Transaction Law No. 1 of 2024 in the context of child protection, (2) to describe the impact of these regulations on TikTok's policies and practices in protecting children from the risks that may arise on the platform. The results of this study are that the European Union's Digital Services Act regulates online platforms with a holistic and comprehensive approach, while the Electronic Information and Transaction Law No. 1 of 2024 focuses more on the Indonesian context. The differences between the two include the definition of child protection, platform obligations, complaint mechanisms, sanctions, and content monitoring approaches. However, both aim to protect children from risks in the digital environment. The impact of both regulations on TikTok's policies and practices includes increased platform obligations and responsibilities, transparency, stricter content monitoring, implementation of effective complaint mechanisms, and closer cooperation with government and relevant agencies.